ON "ROAD MAPS", THE "RANKING RUSH" AND ACADEMIC WRITING - Irina B. Korotkina (Moscow Polytechnic University, 2017)
Abstract. Russian universities are now involved into a severe competition for university rankings with a special focus on academics publishing in international journals. The directive demand from the government meets the understandable response in terms of quantification, which does not reflect the quality of published research, nor does it foster pursuit for such quality. Establishing writing centers in leading universities seems to help solve the problem on the qualitative basis. However, to implement the policy aimed at raising the quality of research papers, Russia needs more than local, optional institutions or even a volunteer association of writing centers, such as the newly established Russian Consortium. To be taken seriously by governmental bodies and the academic community, academic writing ought to be introduced as a discipline taught at all levels of education. The concept of an interuniversity writing center, based on the financial support from universities is considered to be the most appropriate decision at the initial stage of the development of academic writing, for it will unite Russian experts and enable them to work openly and independently for the whole nation, and not only for a particular institution.